Estimation from moments measurements for amyloid depolymerisation. (21st May 2016) - Armiento, Aurora; Doumic, Marie; Moireau, Philippe; Rezaei, H.
Abstract: Estimating reaction rates and size distributions of protein polymers is an important step for understanding the mechanisms of protein misfolding and aggregation, a key feature for amyloid diseases. This study aims at setting this framework problem when the experimental measurements consist in the time-dynamics of a moment of the population (i.e. for instance the total polymerised mass, as in Thioflavin T measurements, or the second moment measured by Static Light Scattering). We propose a general methodology, and we solve the problem theoretically and numerically in the case of a depolymerising system. We then apply our method to experimental data of depolymerising oligomers, and conclude that smaller aggregates of ovPrP protein should be more stable than larger ones. This has an important biological implication, since it is commonly admitted that small oligomers constitute the most cytotoxic species during prion misfolding process. Abstract : Graphical abstract: Structural model of PrP O1 oligomer depolymerization into α-enriched monomeric PrP as explored in the present work. Abstract : Highlights: A framework methodology for estimating cluster concentration in protein aggregation. Theoretical solution with kernel method in a depolymerising system. Theoretical solution with 4dVar data assimilation method in a depolymerising system. Our moment-based method is tested on experimental data of ovPrP oligomers. Smaller aggregates, which are probably the most cytotoxic species, reveal more stable.